The Effect of Tax Counseling and Tax Services on Tax Compliance of Personal Persons in Indonesia - Yasir Iswanto; I Nyoman Sumaryadi; Mansyur Achmad; Faria Ruhana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of the study was to examine and determine the magnitude of the effect of tax counseling and services on individual taxpayers' tax compliance. The research uses a quantitative research approach. The research sample of 100 respondents was taken from the research population of 16,850,000 tax payers using the slovin formula. Data collection techniques using library research, questionnaire techniques and observation. Data analysis used frequency distribution, validity and reliability test, simple regression analysis and multiple regression. The results showed that the magnitude of the effect of tax counseling on tax compliance which reached 12.5 percent was determined by communicated tax knowledge, attitude and politeness, level of clarity explained, cooperation with other institutions/parties, attitude and politeness, level of clarity of answers, friendliness. , and the direction given (social, technical); The magnitude of the influence of tax services on tax compliance which reached 63.5 percent is determined by regulations regarding the provision of convenience of deposit, regulations regarding the provision of ease of reporting, Mobile Tax Units, piloting public service malls (MPP), piloting tax kiosks, attitudes and politeness, consultation and guidance. , timeliness of completion, and comfort of the service room; and there is a positive and significant effect between tax counseling and tax services together on tax compliance. The contribution of the effect of taxation services (0.556) is greater than the contribution of the effect of tax counseling (0.398) to tax compliance.